Electrochemical Oxidation of Lithium Carbonate Generates Singlet Oxygen. Issue 19 (14th April 2018) - Mahne, Nika; Renfrew, Sara E.; McCloskey, Bryan D.; Freunberger, Stefan A.
Abstract: Solid alkali metal carbonates are universal passivation layer components of intercalation battery materials and common side products in metal‐O2 batteries, and are believed to form and decompose reversibly in metal‐O2 /CO2 cells. In these cathodes, Li2 CO3 decomposes to CO2 when exposed to potentials above 3.8 V vs. Li/Li + . However, O2 evolution, as would be expected according to the decomposition reaction 2 Li2 CO3 →4 Li + +4 e − +2 CO2 +O2, is not detected. O atoms are thus unaccounted for, which was previously ascribed to unidentified parasitic reactions. Here, we show that highly reactive singlet oxygen ( 1 O2 ) forms upon oxidizing Li2 CO3 in an aprotic electrolyte and therefore does not evolve as O2 . These results have substantial implications for the long‐term cyclability of batteries: they underpin the importance of avoiding 1 O2 in metal‐O2 batteries, question the possibility of a reversible metal‐O2 /CO2 battery based on a carbonate discharge product, and help explain the interfacial reactivity of transition‐metal cathodes with residual Li2 CO3 . Abstract : Knowledge is power : Lithium carbonate is ubiquitous in Li battery systems. Evidence is provided that highly reactive singlet oxygen forms when Li2 CO3 is electrochemically decomposed beyond 3.8 V vs. Li/Li +, which suggests that most currently studied cathodes will be deleteriously affected by Li2 CO3 . Strategies to mitigate 1 O2 formation or the presence of Li2 CO3 during battery operation are therefore warranted.